INFLUENCE OF LEMON NANOEMULSION IN FILMS GELATIN-BASED - Nunes, Juliana C. [UNESP]; Melo, Pamela Thais S. [UNESP]; Aouada, Fauze A. [UNESP]; Moura, Marcia R. de [UNESP] (Soc Brasileira Quimica, 2018)
The development of films from natural polymers is an alternative to reduce the consumption of packaging obtained from non-renewable sources. The formation of edible films requires a polymeric material that forms a homogeneous and continuous matrix. The gelatin is a natural polymer, cheap and abundant, characteristics that instigate its use. The aim of this study was preparing and characterize gelatin films and evaluate the influence of lemon essential oil nanoemulsion on gelatin matrix for an innovative application of the product. The films were characterized for their water vapor permeability (WVP) test, contact angle, thickness and mechanical analysis (tensile strength and elongation at break). The particle size showed an average of 170.6 nm and zeta potential around -10.9 mV. The incorporation of lemon nanoemulsion increased the water vapor permeability of the gelatin and the elongation, but decreased tensile strength due to the interaction with the hydrophobic portion of the polymer matrix.
Keywords: gelatin; lemon essential oil; nanoemulsion